Karakteristik Kepribadian Guru BK di SMK Mandiri Tembung - Afnita Marni Siregar; Yenti Arsini; Linri L (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Â In Islam, counseling is a complete way of thinking about life. Ideas that can help human enjoyment, comfort, and satisfaction. Ideas have the power to lead humans along the best path to become an ideal human being, the path of self-actualization. Counselors must have at least four competencies, including instructional competencies, personal competencies, social competencies, and professional competencies, to be successful. The purpose of this study was to find out whether the counseling teachers at SMK Mandiri Tembung had good personalities in providing counseling services at school. Data collection techniques used are literature review and observation. As for the subject of research is counseling teachers at SMK Mandiri Tembung. The results of the study show that counseling teachers at SMK Mandiri Tembung already have good personality characteristics.